2013
DOI: 10.2527/jas.2013-6235
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of slaughter precocity, carcass weight, and carcass weight gain in Chianina, Marchigiana, and Romagnola young bulls under protected geographical indication1

Abstract: The aim of this study was to estimate the heritability and genetic correlation of age at slaughter (AS), as an indicator of slaughter precocity, carcass weight (CW), and CW gain (CWG = CW × AS(-1)) obtained from young bulls of 3 Italian autochthonous beef cattle breeds [i.e., Chianina (CHI), Marchigiana (MAR), and Romagnola (ROM)]. In addition, the study aimed at evaluating the effect of corrected or uncorrected CW for AS, and analyzing the relationship between adjusted or unadjusted CW with CWG in term of cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
6
10
0
Order By: Relevance
“…The majority of the young bulls and heifers are reared on smallmedium farms, and both the cow-calf and fattening phases have one of the highest gross margins per cow in the EU [24]. The performance traits measured in this study are very similar to those reported in a previous large survey of more than 20,000 animals [14], which also found that Chianina cattle have a greater carcass weight than the Romagnola (430 kg vs. 367 kg, respectively),…”
Section: Animal Performance and Meat Quality Traitssupporting
confidence: 76%
See 2 more Smart Citations
“…The majority of the young bulls and heifers are reared on smallmedium farms, and both the cow-calf and fattening phases have one of the highest gross margins per cow in the EU [24]. The performance traits measured in this study are very similar to those reported in a previous large survey of more than 20,000 animals [14], which also found that Chianina cattle have a greater carcass weight than the Romagnola (430 kg vs. 367 kg, respectively),…”
Section: Animal Performance and Meat Quality Traitssupporting
confidence: 76%
“…Slaughter date is decided by the farmer for each animal individually according to local market requirements, i.e. at carcass fatness scores of about 2.0 for young bulls and 2.5 for young heifers [14] on the European SEUROP carcass classification system [15].…”
Section: Farms and Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also the BW at slaughter showed a progressive increase during the last decades, probably due to: i) the increase of average BW at purchase; ii) the need to dilute the negative differential between purchase and sale prices per kg in a higher BW gain; iii) the genetic improvement of mature size as an indirect response to selec-tion for increased growth rate (Perry and Arthur, 2000); iv) the delayed tendency for fat deposition caused by increased muscular development potential (Renand et al, 1996;Sbarra et al, 2013). The only partial exception to this regard concerned LI young bulls, that evidenced only a slight increase of final BW in the last 30 years.…”
Section: Beef Heifers (Charolais)mentioning
confidence: 99%
“…Silages are prohibited during the last two months of fattening. Slaughter date is decided by the farmer for each animal individually according to local market requirements, i.e., at carcass fatness scores of about 2.0 for young bulls and 2.5 for young heifers [14] on the European SEUROP carcass classification system [15].…”
Section: Farms and Animalsmentioning
confidence: 99%